Roblox Addiction and The Role of Escapism Among Emerging Adults in Jabodetabek - Alleshandra Atthaya Vebrina AS; Linda Wati (Psychological Research and Intervention, 2026)
Online games can make users feel happy because it offers a sense of psychological satisfaction such as not thinking about social pressure, anxiety, frustration, and it gives happiness. Online games are currently widely used among certain groups in Indonesia such as Roblox. Online gaming addiction is a condition in which individuals feel an excessive dependence on online games, potentially causing negative effects on themselves, while escapism is a condition in which a person has a desire or tendency to avoid reality by seeking entertainment and peace of mind. This study aims to examine the relationship between escapism and online gaming addiction by distinguishing two dimensions of motivation, self-expansion and self- suppression. This study uses a quantitative method with participants aged 18-29 lives in Jakarta, Bogor, Depok, Tangerang, or Bekasi. The participants in this study were individuals in states emerging adulthood who played Roblox for at least 4 hours a day. The measurement tools used in this study were the Gaming Addiction Scale by Lemmens et al. (2009) with 7 dimensions and the Escapism Motivation Scale by Stenseng et al. (2021) with 2 dimensions. The results of this study show a significant positive correlation between the Self-Suppression dimension and Online Gaming Addiction (r = 0.594). Individuals who escape based on the pressures or problems (self-suppression) they tend to have an increased level of addiction to online games.